Evaluasi Defect pada Makanan Ringan Kacang Atom Oven - Digitha Oktaviani Putri; Kukuh Setya Widodo; Ken Erliana; Primahasmi Dalulia (Journal of Industrial View, 2025)
Quality is one of the factors that can determine the success of a product in order to penetrate its market, besides that quality is also used as a reference for whether or not a product is suitable for use or consumption. One of the efforts to maintain quality is by implementing strict quality control so that defects do not occur. There are several defects in the production process of oven sukro beans such as burnt, overcooked, coupled, broken, and without ose. The type of broken defect is the highest type of defect of 764 kg. From the results of the analysis using 5 why analysis methods, it was found that 4 root causes of broken defects such as the setting of the coating machine carried out by employees is still not in accordance with the provisions, the operator does not understand the inline roasting ignition standards, raw materials that are often changed, and the lack of supervision from the PIC on employees in carrying out the jobdesk. The factors that cause the type of defect to break are human and material. The results of FMEA method based on RPN number show that setting coating machine is priority to be solved   Kualitas merupakan salah satu faktor yang dapat menentukan keberhasilan dari suatu produk agar menembus pasarnya, selain itu kualitas juga dijadikan sebagai acuan layak atau tidaknya suatu produk untuk dipakai atau dikonsumsi. Upaya untuk menjaga kualitas yaitu salah satunya dengan menerapkan pengendalian kualitas secara ketat agar tidak terjadi defect. Terdapat beberapa defect pada proses produksi kacang sukro oven seperti gosong, overcook, gandeng, pecah, dan tanpa ose. Jenis defect pecah merupakan jenis defect tertinggi sebanyak 764 kg. Dari hasil analisis menggunakan 5 why analysis dan ditemukan 4 akar penyebab terjadinya defect pecah seperti setting mesin coating yang dilakukan karyawan masih kurang sesuai dengan ketentuan, operator kurang memahami standar pengapian roasting inline, bahan baku yang sering ganti, kurangnya pengawasan dari PIC terhadap karyawan dalam melaksanakan jobdesk. Faktor-faktor penyebab jenis defect pecah disebabkan manusia dan material. Hasil analisis FMEA berdasarkan nilai RPN terbesar menunjukkan prioritas penanganan penyebab masalah adalah pada setting mesin coating yang dilakukan karyawan masih kurang sesuai dengan ketentuan